627 Trends and Patterns of Neurosurgery Influencers on Instagram: Increasing a Neurosurgeon's Social Media Footprint. (April 2023) - Pando, Alejandro; Gabriel, Phabinly; Patel, Aman; Talbot, Christopher; Liu, James K.
Abstract : INTRODUCTION: Neurosurgery is a highly technical field and Instagram provides the dissemination of information to a large audience. Misleading information can potentially be harmful. METHODS: A social media tracking tool (Influencity, Madrid, Spain) was used to compile a list of the top neurosurgeon Instagram profiles based on number of followers, average interaction, and engagement obtained between May 2022 and June 2022. Profiles that were professional groups/societies/academic centers, not in the United States, had less than 1000 followers, and those not belonging to board-certified neurological surgeons were excluded. Individual posts were categorized as (1) clinical or professional, (2) lifestyle, or (3) patient-centered. Data such as number of followers, likes, comments, hashtags, caption words, user engagement, average user activity, interests, posts, and Instagram verification were collected and analyzed. RESULTS: A total of 84 neurological surgeon "influencer" Instagram profiles were identified. Of the most recent 30 posts for each influencer, clinical and professional posts made up 61.60%, lifestyle posts made up 29.41%, and patient posts made up 1.77%. The most frequent hashtags were #neurosurgery, #medicine, and #surgery. When comparing the 30 profiles with the most followers to the rest of the field, average interaction (437.13 vs. 136.44; p < 0.001), uploads (569.43 vs 199.65; p = 0.003), likes given in the top posts (791.16 vs 217.78; p < 0.001), and comments given in the top posts (32.67 vs 17.19; p = 0.03) were significantly higher in the top 30. Although the top 30 profiles had an average increased posts per week (2.15 vs. 1.34; p = 0.18) posts per month (8.06 vs. 4.87; p = 0.16), and lifestyle posts (3.9 vs. 2.83), those were not significant. CONCLUSIONS: Neurosurgeons may be able to increase their footprint and reach a wider audience by increasing their upload rate. Our analyses found that most neurosurgeons' posts are centered around clinical and professional interests.